2013
DOI: 10.1039/c2cc37550h
|View full text |Cite
|
Sign up to set email alerts
|

Painting proteins blue: β-(1-azulenyl)-l-alanine as a probe for studying protein–protein interactions

Abstract: We demonstrated that β-(1-Azulenyl)-L-Alanine, a fluorescent pseudoisosteric analog of tryptophan, exhibits weak environmental dependence and thus allows for using weak intrinsic quenchers, such as methionines, to monitor protein-protein interactions while not perturbing them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 30 publications
4
41
0
2
Order By: Relevance
“…[2] Compared to other donors such as the heme cofactor, AzAla is small and thus allows for ap recise localization of the VET starting point. AzAla is pseudo-isosteric to Tr pa nd has been utilized in fluorescence studies because its signal can be separated from that of Tr p. [23][24][25] With similar quantum yields to Tr p, its emission photophysics are more simple and its photostability is superior. Ther esponse of its azide side chain can be monitored by IR spectroscopy,a nd is well separated from native protein and peptide responses.…”
Section: Anisotropicvibrationalenergytransfer(vet)isexpectedtomentioning
confidence: 99%
See 1 more Smart Citation
“…[2] Compared to other donors such as the heme cofactor, AzAla is small and thus allows for ap recise localization of the VET starting point. AzAla is pseudo-isosteric to Tr pa nd has been utilized in fluorescence studies because its signal can be separated from that of Tr p. [23][24][25] With similar quantum yields to Tr p, its emission photophysics are more simple and its photostability is superior. Ther esponse of its azide side chain can be monitored by IR spectroscopy,a nd is well separated from native protein and peptide responses.…”
Section: Anisotropicvibrationalenergytransfer(vet)isexpectedtomentioning
confidence: 99%
“…Endowed with these unique characteristics,A zAla presents ak ey tool to study VET in proteins.C ompleting the donor-sensor pair, the ncAA l-azidohomoalanine (Aha;F igure 1a)r epresents aw ell-suited VET sensor. [2,23,25] To enable these versatile applications in complex proteins, an AzAla-specific orthogonal pair needs to be developed. [2] Aside from being the key tool for VET studies in proteins,t he demand for the incorporation of AzAla is fueled by its properties as af luorescent label.…”
Section: Anisotropicvibrationalenergytransfer(vet)isexpectedtomentioning
confidence: 99%
“…Recently, we reported that β‐(1‐azulenyl)‐L‐alanine (AzAla), a minimally disruptive mimic of tryptophan (Figure ), can be successfully incorporated into calmodulin‐binding peptides without loss of function . While being a structurally conservative replacement, AzAla has a number of unique spectral and photophysical characteristics compared to Trp.…”
Section: Introductionmentioning
confidence: 99%
“…The many tryptophan analogs reported throughout the years still possess the same properties [3,4]. Recently we demonstrated that β-(1-azulenyl)-L-alanine (AzAla), a tryptophan mimic, can serve as an excellent alternative to tryptophan [5]. Fluorescence properties of AzAla are not dependent on the local environment and allow for observation of very small effects exerted by the weak native quenchers inherently present in many proteins, such as histidine and methionine.…”
Section: Fluorescence Probesmentioning
confidence: 99%
“…Incorporation of AzAla into smooth muscle myosin light chain kinase fragment did not perturb its interaction with calmodulin (CaM), moreover weak quenching of AzAla fluorescence by the methionines present in CaM allows for easy and straightforward determination of binding stoichiometry and K d for this interaction [5]. Substitution of the indole by azulene does not influence the functional properties of antimicrobial peptides: the native and AzAla-substituted melittin show essentially identical CD spectra in the presence and in the absence of lipid bilayer and have very similar MIC values in bacterial inner and outer membrane permeabilization assays [6].…”
Section: Fluorescence Probesmentioning
confidence: 99%